Investigation of the Resistance Force Acting on a Sailing Craft in the Case of a Change of Draft Caused by a Change of Powertrain Using Numerical CFD Simulations - Ficzere, Péter; Lévai, Emese (International Journal of Engineering and Management Sciences, 2021)
Nowdays In the case of recreational craft, interfering with motor drive solutions is a common workflow due to increasingly strict rules for environmental reasons. When switching from an internal combustion engine to an electric engine, the change in draft varies from boat to boat, but it can be said in all cases that as the mass changes, so does the draft. Because of this, the magnitude of the resistance force acting on the ship also varies. In this paper, we examine, through a specific example, the benefits of a change in dive caused by weight gain at different travel speeds.